2016
DOI: 10.1016/j.actatropica.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gastrointestinal transit after infection with different loads of Strongyloides venezuelensis in rats

Abstract: The aim was to correlate the gastrointestinal transit profile in rats, evaluated by a biomagnetic technique, in response to infection with different loads of Strongyloides venezuelensis. Eggs per gram, intestinal number of worms and fecundity, and also gastric emptying time, cecum arrival time, small intestinal transit time and stool weight were determined. Assessments occurred at 0 (control), 3, 6, 9, 12, 15, 18 and 21 days post infection (dpi) with three infective loads (400, 2000, and 10,000 L). Gastric emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It seems that at the peak of infection, EA exerted regulatory effects on gastric emptying and intestinal transit, bringing them to levels comparable with those observed in uninfected control animals. 26 On the other hand, EA did not impact parameters such as stool weight, water and food intake, or weight growth rate throughout the experiment.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…It seems that at the peak of infection, EA exerted regulatory effects on gastric emptying and intestinal transit, bringing them to levels comparable with those observed in uninfected control animals. 26 On the other hand, EA did not impact parameters such as stool weight, water and food intake, or weight growth rate throughout the experiment.…”
Section: Discussionmentioning
confidence: 84%
“…Treatment at both acupuncture points increases the number of worms at 21 dpi and does not contribute to eradication of the infection, since the profile after EA is similar to that observed in untreated rats. 26 It is possible that Original paper acupuncture could modulate the adaptive immune response by altering the balance of Th1/Th2 T helper cells in disease states to maintain homeostasis. 42 The immune response to Strongyloides species is characterised by the production of Th2-type cytokines 21 and it has been suggested that sequential EA stimulation at ST36 suppresses the production of these cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations